A Critical Evaluation of the Relationship between Motivation and Staff Absenteeism in Infosys BPO, India. - Krishna Swamy, Venkata Subramaniam (2010)
The purpose of this research is to critically evaluate the relationship between motivation and staff absenteeism in Infosys BPO. In the introduction the researcher explains about the background of the company, the objectives and the structure of the research by telling the key points of the chapters. Through the review of concepts the researcher was able to easily understand the relationship between motivation of how people are being motivated and then what leads to the level of staff absence.